2021
DOI: 10.3390/foods11010098
|View full text |Cite
|
Sign up to set email alerts
|

The Main Anthocyanin Monomer from Lycium ruthenicum Murray Fruit Mediates Obesity via Modulating the Gut Microbiota and Improving the Intestinal Barrier

Abstract: Anthocyanins have been shown to exert certain antiobesity properties, but the specific relationship between anthocyanin-induced beneficial effects and the gut microbiota remains unclear. Petunidin-3-O-[rhamnopyranosyl-(trans-p-coumaroyl)]-5-O-(β-D-glucopyranoside) (P3G) is the main anthocyanin monomer from the fruit of Lycium ruthenicum Murray. Therefore, in this study, we investigated the antiobesity and remodeling effects of P3G on gut microbiota through a high-fat diet (HFD)-induced obesity mouse model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…It is believed that the production of butyric acid is mainly contributed by Lachnospiraceae and Ruminococcaceae , among which Ruminococcaceae is a mucin-degrading bacterium that can ferment carbohydrates to produce butyrates . In the present study, we found that the interventions with CGA, EBE, and ELE significantly increased the relative abundance of Ruminococcaceae in mice, which is consistent with their n -butyric acid content and the results of the SCFA receptor gene assay and is in line with the findings of previous studies. , Therefore, the presence of EBE and ELE in the gut microbiome can stimulate butyric acid production, alleviate lipid metabolism disorders, and promote lipid breakdown in adipocytes by increasing the relative abundance of Ruminococcaceae . The gut microbiome can have a direct impact on gene expression in the body, and approximately 99% of the genes detected in human organs are of microbial origin. , Therefore, the mechanisms through which Desulfovibrionaceae , Erysipelotrichaceae , and Ruminococcaceae act may be linked to changes at the molecular and genetic levels.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is believed that the production of butyric acid is mainly contributed by Lachnospiraceae and Ruminococcaceae , among which Ruminococcaceae is a mucin-degrading bacterium that can ferment carbohydrates to produce butyrates . In the present study, we found that the interventions with CGA, EBE, and ELE significantly increased the relative abundance of Ruminococcaceae in mice, which is consistent with their n -butyric acid content and the results of the SCFA receptor gene assay and is in line with the findings of previous studies. , Therefore, the presence of EBE and ELE in the gut microbiome can stimulate butyric acid production, alleviate lipid metabolism disorders, and promote lipid breakdown in adipocytes by increasing the relative abundance of Ruminococcaceae . The gut microbiome can have a direct impact on gene expression in the body, and approximately 99% of the genes detected in human organs are of microbial origin. , Therefore, the mechanisms through which Desulfovibrionaceae , Erysipelotrichaceae , and Ruminococcaceae act may be linked to changes at the molecular and genetic levels.…”
Section: Discussionsupporting
confidence: 93%
“…50 The study by Liu et al demonstrated that the weight loss effect of the monomer compound P3G in anthocyanins was related to its regulatory effect on Erysipelotrichaceae, resulting in a reduction in the relative abundance of Erysipelotrichaceae in mice fed an HFD. 44 Similarly, another study by Wang et al showed that CGA intervention alleviated HFD-induced lipid metabolism disorders by significantly reducing the relative abundance of Erysipelotrichaceae. 55 In addition, the study by Zietak et al also showed that a decrease in the relative abundance of Erysipelotrichaceae was positively correlated with leanness.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3- O -[6- O -(4- O -(trans-p-coumaroyl)-a- l -rhamnopyranosyl)-b- d -glucopyranoside]-5- O - [b- d -glucopyranoside] ( Figure S1 ) is considered to be the main component of anthocyanin from the fruits of L. ruthenicum [ 13 , 14 ]. It has been reported that anthocyanins from the fruits of L. ruthenicum (ACN) possess a wide range of biological functions, including antioxidant and anti-inflammatory properties and can change the gut microbiota and reduce the risk of chronic diseases, such as obesity [ 15 , 16 , 17 ]. However, the role of ACN in the prevention of obesity is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The representative bioactive ingredients in the fruit of LR are anthocyanins [ 6 ]. The health benefits of LR anthocyanins (LRA) have been extensively studied, such as their antioxidant [ 7 ], anti-inflammatory [ 8 ], anti-gouty arthritis [ 9 ], liver-protection [ 10 ], hypoglycemic [ 11 ], anti-obesity [ 12 ], and gut microbiota modulation [ 13 , 14 ] benefits. In addition, our previous work showed that LRA could relieve aging-related memory impairment and hippocampal damage in a D-galactose (DG)-induced accelerated aging rat model [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%